ANCA-negative Churg-Strauss Syndrome - Abdal, Syed Jamil; Sarker, Md. Zilan Miah; Ali, Syed Md. Monowar; Bhuiyan, A. K. M. Motiur Rahman; Shazzad, Md. Nahiduzzaman (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
A rare and a disease of unknown etiology, Churg-Strauss syndrome (CSS) is a granulomatous necrotizing small vessel vasculitis characterized by the presence of asthma, sinusitis, and hypereosinophilia, which is initially described by Churg and Strauss in 1951. Because of its clinical and pathological features that overlap with those of the other anti-neutrophil antibody (ANCA)-associated systemic vasculitides (AASVs) and now the disease is classified as AASVs. The ANCA status may dictate the clinical phenotype. ANCA-positive patients are significantly more likely to have disease manifestations associated with small-vessel vasculitis, including oecrotising glomemlonephritis, mononeuritis and purpura, whereas ANCA-negative cases predominantly likely to have cardiac and lung involvement. The objective of this case report is to point out the possibility of vasculitic rash in ANCA-negative CSS in a 35-year-old man and the disease rarely occurs in Bangladeshi population. We analyze the history, clinical examinations and relevant investigations related to the patient to establish the diagnosis in our department. The clinical scenario and biopsy help us to attain the diagnosis. But due to unavailability of patients' cohort we have limitations of comparison of ANCA status in Bangladeshi populations. Though ANCA-positive and ANCA-negative CSS differ phenotypically, primary therapy for both the conditions is systemic glucocorticoids. Additional immunosuppressive agents like cyclophosphamide, mycophenolate mofetil, azathioprine, rituxin1ab are occasionally added in patients with more advanced or refractory disease.